Monomolecular films of cholesterol oxidase and S-Layer proteins - Ferraz, Helen Conceicao; Guimaraes, Juliana Aguilar; Moitinho Alves, Tito Livio; Leopoldo Constantino, Carlos Jose [UNESP] (Elsevier B.V., 2011)
Cholesterol oxidase (ChOx) is a flavoenzyme that catalyzes the oxidation of cholesterol to cholest-5-en-3-one and subsequently the isomerization to cholest-4-en-3-one. ChOx has been very commonly studied as the detection element in cholesterol biosensors. In the biosensor development field, a relatively new approach is the use of crystalline bacterial cell surface layers, known as S-Layer proteins. These proteins exhibit the ability of self-assembling at surfaces, opening a vast spectrum of applications, both in basic and applied researches. In our study, monomolecular films of ChOx and mixed films of ChOx/S-Layer proteins and DPPC/S-Layer proteins were produced using the Langmuir technique. Characterization of the films was performed by means of surface pressure-molecular area (pi-A) isotherms. Stable monolayers were obtained, which means that they can be transferred to solid substrates by Langmuir-Blodgett technique. Mixed monolayers showed an ideal like behavior. (C) 2011 Elsevier B. V. All rights reserved.
Keywords: Cholesterol; Cholesterol oxidase; S-Layer proteins; Monolayer; Biosensor